Peran Teman Sebaya Terhadap Penyimpangan Sosial Remaja di Desa Beleka Kabupaten Lombok Barat - Sulistia Zikrotul Qolbi; Hamidsyukrie ZM; Suud (Universitas Hamzanwadi, 2026)
This study aims to understand the role of peers in deviant social behavior among vulnerable adolescents aged 12-21 years. Adolescence is a period of self-discovery that is greatly influenced by the social environment, especially peer groups. During this phase, the need to be accepted and recognized often makes adolescents easily influenced by the behavior of their group. This study uses a qualitative approach with a case study method to explore in depth the dynamics of peer relationships that trigger deviant behavior such as alcohol consumption, drug abuse, and online gambling. The research subjects consisted of adolescents who committed deviant acts and their peers who also committed deviant acts. Data were collected through in-depth interviews, non-participatory observation, and documentation, then analyzed interactively using Miles and Huberman’s method. The results show that peers have a dominant influence on the emergence of deviant behavior, either through direct invitation, habituation, or social pressure within the group. Conversely, peer groups with positive norms can act as a protective factor that helps adolescents avoid deviant behavior. These findings emphasize the importance of the role of family, school, and community in building a social environment that supports positive adolescent development and strengthens supervision of peer interactions.